Mutational analysis of patients with adenomatous polyposis: Identical inactivating mutations in unrelated individuals - Groden, Joanna (1993)
Samples of constitutional DNA from 60 unrelated patients with adenomatous polyposis coli (APC) were examined for mutations in the APC gene. Five inactivating mutations were observed among 12 individuals with APC; all were different from the six inactivating mutations previously reported in this panel of patients. The newly discovered mutations included single-nucleotide substitutions leading to stop codons and small deletions leading to frameshifts. Two of the mutations were observed in multiple APC families and in sporadic cases of APC; allele-specific PCR primers were designed for detecting mutations at these common sites. No missense mutations that segregated with the disease were found.